Nilai-Nilai Moderasi Beragama Dalam Buku Teks Al-Qur'an Hadits Kelas XI Terbitan Kemenag RI Tahun 2020 - Hasanah, Amalia; Rohimah, Siti (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2024)
Religious moderation is the key to the emergence of balance for the maintenance of civilisation that creates peace, so it is necessary to instill the values of religious moderation to students, including through textbooks. The data source of this research is the textbook of al-Qur'an hadis class XI Madrasah Aliyah published by the Ministry of Religious Affairs of the Republic of Indonesia in 2000. The research method used in this study uses the library research method, which is research based on processed manuscripts (manuscript studies), facts and primary and secondary data (supporting data) related to the focus of research. The results of this study indicate that nine values of religious moderation namely tawasuth, i'tidal, tasamuh, shura, ishlah, qudwah, muwathanah, al-la'unf and i'tiraf al-'urf have been contained in the textbook, although the number of distribution of these values has not been evenly distributed. This research can be useful in fostering the values of religious moderation in students by using the reference of Al-Qur'an Hadith textbooks properly, so that students are able to apply and appreciate the value of religious moderation effectively.